Pelatihan Kewirausahaan Membuat Aneka Olahan Makanan Berbahan Baku Talas Bagi Ibu-Ibu Rumah Tangga Pada Kelurahan Kampung Melayu Kecamatan Sukajadi Kota Pekanbaru - murnawati, murnawati; khairani, zulia; lubis, nurhayani (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
Abstract: Community service activities is carried out in Kampung Melayu subdistrictSukajadi Pekanbaru. The participants consisted of mother-housewife in Kampung Melayusubdistrict Pekanbaru City Sukajadi numbered 25 people. Community service activities aimsto provide knowledge and training: 1). About the making of various foods made from taro 2).Presents and make it more attractive to package food and hygiene. 3). The sale price to theright so as to expand the marketing reach. The training materials provided include:knowledge of basic concepts, types and characteristics of Indonesian food, the manufacture ofvarious types of food made from taro. Manner of presentation and packaging to make it moreattractive and hygiene so worth selling and calculating the selling price. The method used inthis course are: lectures, discussion, demonstration, training/practice. In general,participants attended the training well and excited this is based among other things on thepractice results achieved. After following this activity the participants can have knowledge offood ingredients, types and techniques varied though. Trainees can mengola meatball mealsthat use basic ingredients taro tuber with a variety of techniques though. Trainingparticipants can present and package the food so that it becomes more attractive and hygiene.Trainees can set the selling price with the right food.